Risk attitudes and private business equity - Frank M. Fossen (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Why do people engage in entrepreneurship and commit large parts of their personal wealth to their business, despite comparably low returns and high risk? This paper connects several streams of literature to shed some light on this puzzle and suggests possible future research avenues. Key insights from the literature are that entrepreneurs may operate in imperfect financial markets and that entrepreneurs are less risk-averse than the rest of the population. A focus of this paper is, therefore, on the role of heterogeneous risk attitudes in entrepreneurial decisions, specifically portfolio choice and the entry and exit decisions. Nonpecuniary benefits of entrepreneurship, such as being independent in the workplace, also contribute to an explanation of entrepreneurial behavior.
Keywords: J23; G11; L26; 330; Entrepreneurship; risk aversion; portfolio choice